2022
DOI: 10.2176/jns-nmc.2022-0103
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Profile of 300 Japanese Patients with Diffuse Gliomas Using a Glioma-tailored Gene Panel

Abstract: Rapid technological advances in molecular biology, including next-generation sequencing, have identified key genetic alterations in central nervous system (CNS) tumors. Accordingly, the fifth edition of the World Health Organization (WHO) CNS tumor classification was published in 2021. We analyzed 303 patients with diffuse glioma using an amplicon-based glioma-tailored gene panel for detecting 1p/ 19q codeletion and driver gene mutations such as IDH1/2, TERTp, EGFR, and CDKN2A/B on a single platform. Within gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, this trend is not commonly seen in Chinese patients [ 4 ]. Similarly, Nayuta HIGA et al [ 21 ], utilizing NGS, reported a lower rate of EGFR amplification in GBM in Asian patients compared to those in other regions. Our research confirms a low frequency of EGFR gene mutations in both Groups A and B of our study.…”
Section: Discussionmentioning
confidence: 93%
“…However, this trend is not commonly seen in Chinese patients [ 4 ]. Similarly, Nayuta HIGA et al [ 21 ], utilizing NGS, reported a lower rate of EGFR amplification in GBM in Asian patients compared to those in other regions. Our research confirms a low frequency of EGFR gene mutations in both Groups A and B of our study.…”
Section: Discussionmentioning
confidence: 93%
“… 15 , 16 In cancer, dysfunctional SWI/SNF complexes are intimately associated with tumor development and progression. 17 In gliomas, ARID1A mutations in WHO grade 3 oligodendrocyte tumors are linked to poorer progression‐free survival, 18 yet the role of ARID1A in GBM remains to be fully unraveled.…”
Section: Discussionmentioning
confidence: 99%
“…In the "classic" TCGA (The Cancer Genome Atlas) subtype, there is typically a high frequency of EGFR ampli cation [18], but this is not prevalent in Chinese patients [4]. Another team, Nayuta HIGA et al, [19] using NGS, also reported a lower ampli cation rate of EGFR in GBM in Asian patients compared to other regions. Our experimental results indicate a low frequency of EGFR gene mutations in Groups A and B.…”
Section: Egfr Mutations In the Taiwanese Population In Our Studymentioning
confidence: 99%